(untitled) (Zaporizhzhia Historical Review, 2021)
Religious factors influenced the national revival of the Ukrainians and other peoples of Centrally East Europe, however even in different regions of Ukraine they had different consequences and values. Thus, at Halichina and Bukovina, that were in composition of Austria-Hungary, priests actively resisted the onslaught of state power, and their activity promoted forming of national consciousness and strengthened national motion of the Ukrainians. The activity of church figures had a positive value also in Lithuanian lands which were under the power of Russia. Unlike Halichina and Bukovina in the Ukrainian provinces of the Russian empire the clergy presented interests of the state. Passivity of orthodox priests, and sometimes counteraction to the national revival, slowed forming of national consciousness and weakened national motion.